Clinical features and antimicrobial susceptibility of oral bacteria isolated from the blood cultures of patients with infective endocarditis - Keigo Maeda; Yuzo Hirai; Masanori Nashi; Shinsuke Yamamoto; Naoki Taniike; Toshihiko Takenobu (Journal of Dental Sciences, 2022)
Background/purpose: The epidemiology of infective endocarditis (IE) is under constant change due to the aging society and increases in antimicrobial-resistant pathogens. However, IE remains severe. This study aimed to review the current clinical characteristics of IE and the antimicrobial susceptibility of oral bacteria (OB) isolated from blood cultures to implement appropriate antimicrobial prophylaxis. Materials and methods: We retrospectively investigated the clinical features of 180 patients with IE in whom OB and pathogens except OB (eOB) were identified as causative microorganisms via blood cultures. The susceptibility of the OB group to eight antibiotics was examined by broth microdilution. Results: Among causative microorganisms, the isolation rate of staphylococci was slightly higher than that of OB; however, the difference was not significant (36.7% vs. 33.8%, p = 0.3203). The number of patients with underlying cardiac disease was significantly higher in the OB group than in the eOB group (53.7% vs. 34.1%, p = 0.0113). Only one ampicillin-resistant OB was detected (2.0%). OBs were significantly less susceptible to clarithromycin and azithromycin than to ampicillin (98.0% vs. 66.7% and 98.0% vs. 60.0%, p = 0.0003 and p = 0.0003, respectively). Moreover, OBs were significantly less susceptible to clarithromycin and azithromycin than to clindamycin (66.7% vs. 88.2% and 60.0% vs. 88.2%, p = 0.0301 and p = 0.0217, respectively). Conclusion: OBs were susceptible to ampicillin. However, the susceptibility of OBs to clarithromycin and azithromycin was significantly lower than that to ampicillin and clindamycin. These results are important and should help decisions regarding guide antimicrobial prophylaxis.